2018
DOI: 10.1080/14767058.2018.1509310
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased amnion volume severity on fetal Doppler indices and perinatal outcomes in idiopathic polyhydramnios

Abstract: Our study showed an increase in myocardial performance index and middle cerebral artery peak systolic velocity values and a decrease in middle cerebral artery pulstatility index values, especially in the severe idiopathic polyhydramnios group. Idiopathic polyhydramnios were associated with low first and fifth minute Apgar score. Additionally, the increase in umbilical artery pulstatility index value and the decrease in middle cerebral artery pulstatility index value became more apparent with the increase in am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…The right MPI has not been evaluated by previous studies on cardiac assessment of fetuses with idiopathic polyhydramnios 17,18 . In our study, the right MPI was significantly higher in cases than in controls.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…The right MPI has not been evaluated by previous studies on cardiac assessment of fetuses with idiopathic polyhydramnios 17,18 . In our study, the right MPI was significantly higher in cases than in controls.…”
Section: Discussioncontrasting
confidence: 70%
“…However, the mean left MPI in the mild group was close to that of the control group (0.62 ± 0.10 vs 0.60 ± 0.12). In their study, left IVCT, IVRT, and ET were not individually reported 18 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations